Risk factors associated with depression among HIV positive women at Mama Lucy Kibaki hospital in Nairobi County, Kenya - Jeruto, Esleen; Mogere, Dominic M.; Kerochi, Atei; Maureen, Koech J.; Gwandi, Martin P. (International Journal Of Community Medicine And Public Health, 2022)
Background: Globally, 280 million people are estimated to have depression. Depression has been associated with negative treatment outcomes and reduced quality of life. The study aimed to determine the prevalence and correlates of depression among HIV-positive women at Mama Lucy Kibaki hospital in Kenya. Methods: A facility-based cross-sectional analytical study design that employed a mixed-method approach. The study employed systematic random sampling to select 183 HIV-positive women. The patient health questionnaire (PHQ-9) was used to screen for depression. Data analysis used statistical package for social sciences. Chi-square test and logistic regression were used to test and measure association. Results: The prevalence of possible depression was 35.6%. Depression was significantly associated with food insecurity (AOR=8.186, C.I=2.950-22.718), low income (AOR=3.766, CI=1.088-13.030), physical exercise (AOR=64, CI=0.039-0.627), maladaptive coping style (AOR=9.585, CI=3.100-29.634), stressful life event (AOR=47, CI=0.005-0.088), intimate partner violence (AOR=36, CI=0.086-0.857), opportunistic infections (AOR=5.8, CI=0.081-0.366) and side effects of antiretroviral (AOR=7.6, CI=0.029-0.601). Themes from qualitative findings were; low socioeconomic status, stigma and opportunistic infections Conclusions: The study revealed a high prevalence of depression but they were more likely to be depressed if they were food insecure, had low income, adopted maladaptive coping styles, experienced a stressful event, intimate partner violence, had opportunistic infections and experienced side effects of antiretroviral. Future mental health interventions should focus on these factors in the prevention and management of depression among HIV-positive women.